Bridging the gap in planning indoor pedestrian facilities - Kalakou, S.; Moura, F. (Transport Reviews, 2014)
Pedestrians are currently attracting the interest of various researchers and practitioners, particularly urban and transport planners. Analysis of the pedestrian behavior, environment and modeling has been carried out in diverse instances in the context of pedestrian planning. This paper seeks to identify the content of each of these three research areas and designate the linkages that connect their interests providing insights into planning indoor pedestrian facilities. To achieve this objective, a review of the literature on pedestrians walking indoors and indoor pedestrian environments was conducted. Understanding pedestrian behavior is fundamental in the pedestrian planning process. Principles of decision-making, cognition, wayfinding and flows were studied. When analyzing the pedestrian environment, Space Syntax and wayfinding analysis were found to be established methods that are an integral part of this field. Finally, the majority of the existing modeling approaches were identified. It was found that despite the dynamic evolution of each area, the integration of different research perspectives is weak. The paper concluded with the proposal of a mindmap which brings together all the concepts found in the literature and which should be explored for a more comprehensive planning of indoor pedestrian facilities.